2018
DOI: 10.2176/nmc.oa.2017-0228
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategy Based on Plaque Vulnerability and the Treatment Risk Evaluation for Internal Carotid Artery Stenosis

Abstract: Carotid endarterectomy (CEA) and carotid artery stenting (CAS) are not appropriate treatment procedure for internal carotid artery stenosis (ICAS) in some patients. The importance of plaque vulnerability and the treatment risk evaluation has been reported. We analyzed whether treatment selection contributes to the outcome. We retrospectively examined 121 patients who underwent CEA or CAS. Treatment was selected based on plaque vulnerability and the treatment risk evaluation. We selected CAS for patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Previous studies have reported the double-balloon protection technique for vulnerable lesions [4,30]. This technique is rational but complicated as a routine procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the double-balloon protection technique for vulnerable lesions [4,30]. This technique is rational but complicated as a routine procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque imaging has been developed, and carotid plaque lesions that show hyperintensities on magnetic resonance (MR) images are considered as lesions with IPH [3]. Appropriate surgical treatment is necessary for lesions with IPH [4]. Carotid artery stenting (CAS) is an alternative to carotid endarterectomy (CEA) and is applied in CEA high-risk patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the criteria for selecting patients for surgical prevention of acute cerebrovascular disease among asymptomatic individuals with carotid stenosis are broadly discussed nowadays [13,14]. There have been several studies, where in addition to atherosclerotic ICA stenosis, the morphological structure of the atherosclerotic plaque was taken into consideration [15][16][17][18]. In recent years, researchers have widely investigated vascular inflammatory markers as well as the relationship between their concentration and the risk of developing atherosclerotic complications [19].…”
Section: Highlightsmentioning
confidence: 99%
“…1 – 3) Currently, it is recommended to select the treatment according to the characteristics of the case. 1 , 4 , 5) In cases with a difficult access route, CEA is usually performed, but CAS is sometimes performed in cases with other risk factors. CAS for cases with a difficult access route are classified into two types: CAS in which it is difficult to insert a guiding catheter owing to conditions such as aortic disease or a type III aortic arch 6 , 7) and CAS in which it is difficult to pass a device through a lesion such as severe stenosis or highly tortuous vessels.…”
Section: Introductionmentioning
confidence: 99%